Nomogram to predict prognosis of head and neck rhabdomyosarcoma patients in children and adolescents - Wu, Jinwen; Zeng, Qi (Frontiers in Oncology, 2024)
Purpose: To explore the prognostic factors of head and neck Rhabdomyosarcoma (HNRMS) in children and adolescents and construct a simple but reliable nomogram model for estimating overall survival of patients.Methods: Data of all HNRMS patients during 2004-2018 were identified from the SEER database. Kaplan-Meier method was performed to calculate Overall survival (OS) stratified by subgroups and comparison between subgroups was completed by Log-rank test. Univariate and multivariate Cox regression were employed for identifying independent predictors, which subsequently is used for a predictive model by R software, and the efficacy of the model was evaluated by applying Receiver operating curve (ROC), calibration and Decision curve analysis (DCA).Results: A total of 446 patients were included in the study. The1-,3-, 5-year overall survival (OS) rate of the whole cohort was 90.6%, 80.0%, 75.5% respectively. The results of univariate and multivariate Cox regression analysis indicated that the primary site in parameningeal region, embryonal histology, M1 stage, IRS stage 4, surgery and chemotherapy were significant prognostic factors (all P＜0.05). The performance of nomogram model was validated by discrimination and calibration, with AUC values of 1, 3, 5 years OS of 0.843, 0.851, 0.890, respectively.We constructed a prognostic nomogram model for predicting the OS in HNRMS patients in children and adolescents and this model presented practical and applicable clinical value to predict survival when choosing treatment strategies.